No Tags. No Masterpieces.: Graffiti as a catalyst of individual creativity - Schorr, Björn (Street Art & Urban Creativity, 2019)
Graffiti often receives attention as a social problem. Its potentials and positive influence on the individual or the society are often left aside in the public discourse. This article shows how graffiti, as a catalyst of creativity, shapes one’s personal career. Graffiti enables a unique combination of motoric and psycho-social abilities, which opens up many perspectives and careers for the so-called writer. The paper aims to show and complete with suggestion the value added through graffiti, especially in the areas of education, participation and urban development, both for the individual and for the whole society.